Aspectos sociodemográficos da depressão e utilização de serviços de saúde no Brasil - Geovane da Conceicao Maximo (2010)
Depression is a mental disorder known for a long time, yet largely misunderstood and stigmatized by common sense and by various health professionals. While modern medicine and psychology have advanced considerably in the knowledge of its etiology and its treatment, the prevalence rates of depression are increasing in modern societies, placing this disorder in the ranks of the most striking physical well-being and mental health of the population and rising costs of health care systems in the long term.The World Health Organization figures have shown that approximately 450 million people currently suffer with some type of mental disorder in the world. Of these, 121 million are affected by depression, which equates to something around 2% of the total world population. In Brazil, depression struck in 2008, a contingent of 7.837.541 people (or 4.1% of population).Focusing on the uniqueness epidemiology of depression in Brazil, this work aims to determine whether there is evidence that any person, who self-reported depression at the time of the survey data from PNAD 2008, employ Health Care Services with higher intensity rather than the rest of population.Hence, based on Item Response Theory (IRT), there was a necessity for establishing an intensiveness measure for using The Health Care Services, taking into consideration information on the consumption of medical consultations and hospital admissions (except for those related to childbirth and postpartum period). The measure was dichotomized into two groups according to intensity of employment of Health Care Services, and adopted as the logistic outcome of the regression model that was used to measure the socioeconomic and demographic factors associated with the consumption of those services. The theoretical model of health services utilization by Andersen (1995) was adopted as theoretical work.Results have shown that depression is a factor strongly associated with the consumption of Health Care Services in Brazil. Both individuals who self-reported "just depression" as those who self-reported "depression in addition to other diseases" had higher odds to utilize, with greater intensity, Health Care Services, compared to individuals who did not report any disease. Women, in particular, emerged as the group most vulnerable to depression and also with the greatest need for taking the services at the Health Care System. Moreover, there is a sense that access to and use of Health Care Services in Brazil are still characterized by social inequalities, with individuals of higher socioeconomic status, who have private Health Care insurance and living in urban areas are more likely to use health services .By taking the emergence of depression as a public health problem of the 21st century, the results point for the necessity to promote mental health within primary care in the Health Care System, and educational measures which can demystify the depressive disorder. Nevertheless, it reaffirms also the need for fighting against social inequities on accessing and using of Health Care Services in order to promote a true health to the population.